2017
DOI: 10.1103/physrevd.95.083509
|View full text |Cite
|
Sign up to set email alerts
|

Magnetogenesis during inflation and preheating in the Starobinsky model

Abstract: By assuming the kinetic coupling f 2 (φ)F F of the effective inflaton field φ with the electromagnetic field, we explore magnetogenesis during the inflation and preheating stages in the R 2 Starobinsky model [1]. We consider the case of the exponential coupling function f (φ) = exp(αφ/Mp) and show that for α ∼ 12 − 15 it is possible to generate the large scale magnetic fields with strength 10 −15 Gauss at the present epoch. The spectrum of generated magnetic fields is blue with the spectral index n = 1+s, s > … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 78 publications
4
35
0
Order By: Relevance
“…For decreasing coupling functions, it is well known that the electric energy density dominates the magnetic one [39,40,44] and if we try to generate the magnetic field strong enough to be in accord with the observations, the electric field appears to be even stronger and its energy density exceeds that of the inflaton field. This is known as the backreaction problem.…”
Section: Introductionsupporting
confidence: 55%
“…For decreasing coupling functions, it is well known that the electric energy density dominates the magnetic one [39,40,44] and if we try to generate the magnetic field strong enough to be in accord with the observations, the electric field appears to be even stronger and its energy density exceeds that of the inflaton field. This is known as the backreaction problem.…”
Section: Introductionsupporting
confidence: 55%
“…The inflationary and slow-roll parameters are given by 15) and the inflationary and slow-roll conditions ǫ V ≪ 1 and η V ≪ 1 are both satisfied if e φ/M ≫ 1. In this regime, we have 16) and the slow-roll dynamics (2.13) is described bẏ…”
Section: Inflationary Regimementioning
confidence: 99%
“…The quantities I 2 ± (η) will be assumed to be always positive, in order to avoid instability. 15) and integrating by part in (3.13), we obtain the action 16) and the equation of motion for the Fourier mode of v i with wavenumber k :…”
Section: Lagrangianmentioning
confidence: 99%
“…Moreover, the backreaction of EM fields can modify the inflaton dynamics, change the Universe expansion, and make an impact on the spectrum of primordial perturbations. In our previous work [38], we considered the case of kinetic coupling between the scalar inflaton field and the EM field introduced by Ratra [33] and revisited many times in the literature arXiv:1907.10443v2 [astro-ph.CO] 19 Sep 2019 [37,[39][40][41][42][43][44][45][46][47] and showed that the backreaction of generated electric fields is indeed very important because it strongly suppresses magnetogenesis.…”
Section: Introductionmentioning
confidence: 99%